DABCO-Customized Nanoemulsions: Characterization, Cell Viability and Genotoxicity in Retinal Pigmented Epithelium and Microglia Cells - Ana R. Fernandes; Tiago dos Santos; Pedro L. Granja; Elena Sanchez-Lopez; Antonello Santini; Maria L. Garcia; Amelia M. Silva; Eliana B. Souto (Pharmaceutics, 2021)
Quaternary derivatives of 1,4-diazabicyclo[2.2.2]octane (DABCO) and of quinuclidine surfactants were used to develop oil-in-water nanoemulsions with the purpose of selecting the best long-term stable nanoemulsion for the ocular administration of triamcinolone acetonide (TA). The combination of the best physicochemical properties (i.e., mean droplet size, polydispersity index, zeta potential, osmolality, viscoelastic properties, surface tension) was considered, together with the cell viability assays in ARPE-19 and HMC3 cell lines. Surfactants with cationic properties have been used to tailor the nanoemulsions’ surface for site-specific delivery of drugs to the ocular structure for the delivery of TA. They are tailored for the eye because they have cationic properties that interact with the anionic surface of the eye.